Liquid composition, metallic gloss film and article

A liquid composition with a thiophene polymer, polymeric component, and aprotic solvent improves inkjet ejection and scratch resistance in metallic luster films, addressing the limitations of existing compositions.

JP7609368B2Active Publication Date: 2025-01-07FUJIFILM BUSINESS INNOVATION CORP +1
View PDF 12 Cites 0 Cited by

Patent Information

Application Number
JP2020177527
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2020-10-22
Publication Date
2025-01-07
Estimated Expiration
2040-10-22

AI Technical Summary

Technical Problem

Liquid compositions containing a thiophene polymer and a solvent often exhibit poor inkjet ejection properties and scratch resistance, especially when forming metallic luster films.

Method used

A liquid composition comprising a thiophene polymer, a polymeric component, a polymerization initiator, and an aprotic polar solvent, with specific molecular weight ranges and polymerization methods, enhances inkjet ejection and scratch resistance.

Benefits of technology

The composition achieves superior inkjet ejection properties and scratch resistance in metallic luster films compared to traditional compositions, with improved gloss and stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007609368000001
    Figure 0007609368000001
  • Figure 0007609368000002
    Figure 0007609368000002
Patent Text Reader

Abstract

To provide a liquid composition that forms a metallic luster film having an excellent inkjet ejection property and excellent scratch resistance.SOLUTION: A liquid composition comprises a thiophene polymer and at least one polymerization component selected from a group consisting of a monomer and an oligomer.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure provides a liquid composition, a metallic luster film, and an article. [Background technology]

[0002] Patent Document 1 discloses a method for producing a metallic gloss film made of a thiophene polymer by electrolytic polymerization of a thiophene monomer on a conductor by a potential sweep method. Patent Document 2 discloses a film having metallic luster that contains a thiophene polymer. Patent Document 3 discloses a coating liquid for forming a metallic coating film, which contains polythiophene and is doped with chloride ions or perchlorate ions. Patent Document 4 discloses a film having a gold or copper luster, which contains a thiophene polymer doped with at least one of perchlorate ions, hexafluorophosphate ions, tetrafluoroborate ions, chloride ions, and paratoluenesulfonate ions. Patent Document 5 discloses a solution for producing an article having metallic luster, which contains at least one of a polyester resin, a polycarbonate resin, a polyvinylpyrrolidone resin, a polystyrene resin, a polymethyl methacrylate resin, and a styrene-acrylic copolymer resin, a thiophene polymer, and a solvent. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2017-052856 A [Patent Document 2] JP 2017-110232 A [Patent Document 3] Patent No. 6031197 [Patent Document 4] Patent No. 6308624 [Patent Document 5] JP 2018-012831 A Summary of the Invention [Problem to be solved by the invention]

[0004] A liquid composition containing a thiophene polymer, a resin, and a solvent may have poor ink-jet ejection properties, whereas a metallic gloss film formed using a liquid composition consisting of only a thiophene polymer and a solvent may have poor scratch resistance.

[0005] The embodiments of the present disclosure have been made under the above circumstances. An embodiment of the present disclosure aims to provide a liquid composition that is superior in inkjet ejection properties compared to a liquid composition containing a thiophene polymer, a resin, and a solvent, and that forms a metallic gloss film that is superior in scratch resistance compared to a liquid composition consisting of only a thiophene polymer and a solvent, and an object of the present disclosure is to achieve this. [Means for solving the problem]

[0006] Specific means for solving the above problems include the following aspects. <1> A liquid composition comprising a thiophene polymer and at least one polymerization component selected from the group consisting of monomers and oligomers. <2> The polymerization component includes a chain-polymerizable polymerization component. <1> The liquid composition according to claim 1. <3> Further comprising a polymerization initiator, <1> or <2> The liquid composition according to claim 1. <4> The polymerization initiator includes at least one selected from the group consisting of a thermal radical generator and a photoradical generator. <3> The liquid composition according to claim 1. <5> Further comprising an aprotic polar solvent, <1> ~ <4> 13. The liquid composition according to claim 12 . <6> The aprotic polar solvent includes at least one selected from the group consisting of acetonitrile, nitromethane, γ-butyrolactone, propylene carbonate, N-methylpyrrolidone, dimethylformamide, and dimethylsulfoxide. <5> The liquid composition according to claim 1. <7> The weight average molecular weight of the thiophene polymer is 200 or more and 30,000 or less. <1> ~ <6> 13. The liquid composition according to claim 12 . <8> The weight average molecular weight of the thiophene polymer is 500 or more and 20,000 or less. <7> The liquid composition according to claim 1. <9> The thiophene polymer includes a polymer obtained by polymerizing at least one selected from the group consisting of alkoxythiophenes, alkylthiophenes, aminothiophenes, and hydroxythiophenes. <1> ~ <8> 13. The liquid composition according to claim 12 . <10> the thiophene polymer includes a polymer in which at least an alkoxythiophene is polymerized, and the alkoxythiophene includes an alkoxythiophene having an alkoxy group having 1 to 8 carbon atoms; <9> The liquid composition according to claim 1. <11> the thiophene polymer includes a polymer in which at least an alkylthiophene is polymerized, and the alkylthiophene includes an alkylthiophene having an alkyl group having 1 to 8 carbon atoms; <9> or <10> The liquid composition according to claim 1. <12> <1> ~ <11> 13. A metallic gloss film obtained by curing the liquid composition according to any one of claims 1 to 12. <13> <12> An article having the metallic luster film according to claim 1. Effect of the Invention

[0007] <1> , <2> , <3> , <4> , <5> , <6> , <9> , <10> , <11> According to the present invention, there is provided a liquid composition which has superior ink-jet dischargeability as compared with a liquid composition containing a thiophene polymer, a resin, and a solvent, and which forms a metallic gloss film which has superior scratch resistance as compared with a liquid composition consisting of only a thiophene polymer and a solvent. <7> According to the present invention, a liquid composition is provided which forms a metallic gloss film having excellent gloss, as compared with a liquid composition in which the weight-average molecular weight of the thiophene polymer is less than 200 or more than 30,000. <8> According to the present invention, a liquid composition is provided which forms a metallic gloss film having excellent gloss, as compared with a liquid composition in which the weight-average molecular weight of the thiophene polymer is less than 500 or more than 20,000. <12> According to the method, a metallic luster film having excellent scratch resistance is provided as compared with a metallic luster film formed from a liquid composition consisting of only a thiophene polymer and a solvent. <13> According to the method, an article having a metallic luster film that is superior in scratch resistance to an article having a metallic luster film formed from a liquid composition consisting of only a thiophene polymer and a solvent is provided. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0008] Hereinafter, embodiments of the present disclosure will be described. These descriptions and examples are merely illustrative of the embodiments, and are not intended to limit the scope of the embodiments.

[0009] In the numerical ranges described in the present disclosure in stages, the upper or lower limit value described in one numerical range may be replaced with the upper or lower limit value of another numerical range described in stages. In addition, in the numerical ranges described in the present disclosure, the upper or lower limit value of the numerical range may be replaced with a value shown in the examples.

[0010] In the present disclosure, the term "step" includes not only an independent step, but also a step that cannot be clearly distinguished from other steps, as long as the intended purpose of the step is achieved.

[0011] In the present disclosure, each component may contain multiple types of corresponding substances. When referring to the amount of each component in a composition in the present disclosure, if multiple substances corresponding to each component are present in the composition, the total amount of the multiple substances present in the composition is meant unless otherwise specified.

[0012] <Liquid Composition> The liquid composition according to this embodiment contains a thiophene polymer and at least one polymerization component selected from the group consisting of monomers and oligomers.

[0013] In this embodiment, the oligomer, which is a polymerization component, has a molecular weight of less than 10,000, preferably less than 5,000, and more preferably less than 3,000. In this embodiment, the oligomer, which is a polymerization component, has a molecular weight of preferably 500 or more.

[0014] The liquid composition according to this embodiment preferably has a content of polymers other than thiophene polymers (polymers that are not oligomers and have a molecular weight of 10,000 or more) of less than 30% by mass, more preferably less than 20% by mass, and even more preferably less than 10% by mass, based on the total solid content of the liquid composition.

[0015] The liquid composition according to this embodiment contains at least one of a monomer and an oligomer as a polymerization component, and therefore has a viscosity within an appropriate range and is excellent in ink-jet dischargeability. The liquid composition according to the present embodiment forms a metallic luster film containing a thiophene polymer, and since the metallic luster film is a cured film containing a polymer formed by polymerization of a polymerization component, it has excellent scratch resistance.

[0016] [Thiophene polymer] A thiophene polymer is a polymer formed by polymerizing two or more thiophenes. A film containing a thiophene polymer exhibits a metallic luster because the layer-oriented thiophene polymer reflects light of a specific wavelength.

[0017] The thiophene polymer may be a polymer in which one kind of thiophene is polymerized, or a polymer in which a plurality of kinds of thiophene are polymerized. An example of the thiophene polymer is a polymer represented by the following general formula:

[0018] [ka]

[0019] In the above general formula, R is a substituent, m is 1 or 2, and n is an integer of 2 or more. R may be one type or multiple types. When m is 2, two Rs in one thiophene ring may be the same type or different types. When m is 2, two Rs in one thiophene ring may be linked to form a cyclic group.

[0020] R is, for example, an alkoxy group, an alkyl group, an amino group, a hydroxy group, a hydroxyalkyl group, an aryl group, an allyl group, a cyano group, or a halogeno group. From the viewpoint of more reliably exhibiting metallic luster in a film containing a thiophene polymer, R is preferably an alkoxy group, an alkyl group, an amino group, or a hydroxy group, more preferably an alkoxy group, an alkyl group, or an amino group, and further preferably an alkoxy group or an alkyl group.

[0021] When R is an alkoxy group, the number of carbon atoms in the alkoxy group is preferably 1 or more and 8 or less, more preferably 1 or more and 6 or less, even more preferably 1 or more and 4 or less, and particularly preferably 1 or 2, from the viewpoint of facilitating layer-like orientation of the thiophene polymer. Examples of thiophenes having at least one alkoxy group include 3-methoxythiophene, 3,4-dimethoxythiophene, 3-ethoxythiophene, 3,4-diethoxythiophene, 3-propoxythiophene, 3-butoxythiophene, 3,4-ethylenedioxythiophene, and 3,4-propylenedioxythiophene.

[0022] When R is an alkyl group, the number of carbon atoms in the alkyl group is preferably 1 or more and 12 or less, more preferably 1 or more and 8 or less, even more preferably 1 or more and 6 or less, still more preferably 1 or more and 4 or less, and particularly preferably 1 or 2, from the viewpoint of facilitating the orientation of the thiophene polymer in a layered form. Examples of thiophenes having at least one alkyl group include 3-methylthiophene, 3,4-dimethylthiophene, 3-ethylthiophene, 3,4-diethylthiophene, 3-butylthiophene, 3-hexylthiophene, 3-heptylthiophene, 3-octylthiophene, 3-nonylthiophene, 3-decylthiophene, 3-undecylthiophene, 3-dodecylthiophene, and 3-bromo-4-methylthiophene.

[0023] When R is an amino group, the amino group may be a primary amino group (-NH2) or a secondary amino group (-NHR 1 , R 1 is an alkyl group or an aryl group, preferably an alkyl group; 1 R 2 , R 1 and R 2 are each independently an alkyl group or an aryl group, and an alkyl group is preferable. The number of carbon atoms in the alkyl group in the secondary amino group or tertiary amino group is preferably 1 or 2 from the viewpoint of facilitating the orientation of the thiophene polymer in a layer form. Examples of thiophenes having at least one amino group include 3-aminothiophene, 3,4-diaminothiophene, 3-methylaminothiophene, and 3-dimethylaminothiophene.

[0024] As the thiophene polymer, from the viewpoint that the film containing the thiophene polymer exhibits metallic luster more reliably, a polymer in which at least one selected from the group consisting of alkoxythiophenes, alkylthiophenes, aminothiophenes and hydroxythiophenes is polymerized is preferable, a polymer in which at least one selected from the group consisting of alkoxythiophenes and alkylthiophenes is polymerized is more preferable, and poly(alkoxythiophenes) in which only alkoxythiophenes are polymerized, poly(alkylthiophenes) in which only alkylthiophenes are polymerized, or poly(alkylthiophenes) (alkoxythiophenes) in which only alkylthiophenes and alkoxythiophenes are polymerized are even more preferable. The number of carbon atoms of the alkoxy group in the alkoxythiophene is preferably 1 to 8, more preferably 1 to 6, even more preferably 1 to 4, and particularly preferably 1 or 2. The number of carbon atoms of the alkyl group in the alkylthiophene is preferably 1 to 12, more preferably 1 to 8, even more preferably 1 to 6, even more preferably 1 to 4, and particularly preferably 1 or 2.

[0025] The thiophene polymer preferably has a weight average molecular weight of 200 or more and 30,000 or less, more preferably 500 or more and 20,000 or less, and even more preferably 1,000 or more and 10,000 or less, from the viewpoint of facilitating layer-like orientation of the thiophene polymer.

[0026] The molecular weight of the thiophene polymer is measured by gel permeation chromatography (GPC) using a Tosoh Corporation HPLC1100 as the measuring device, two Tosoh Corporation TSKgel GMHHR-M (inner diameter 7.8 mm, length 30 cm) columns arranged in series, chloroform as the solvent, and monodisperse polystyrene as the standard sample.

[0027] The content of the thiophene polymer in the liquid composition according to this embodiment is preferably from 0.1% by mass to 99.9% by mass, more preferably from 0.5% by mass to 99% by mass, and even more preferably from 10% by mass to 95% by mass, based on the total solid content of the liquid composition.

[0028] The thiophene polymer is synthesized, for example, by oxidative polymerization, which is a method for polymerizing thiophenes in a liquid or solid phase using an oxidizing agent.

[0029] Examples of the oxidizing agent include ferric salts, cupric salts, cerium salts, dichromates, permanganates, ammonium persulfate, boron trifluoride, bromates, hydrogen peroxide, chlorine, bromine, and iodine.

[0030] The oxidizing agent is preferably a ferric salt, which may be in the form of a hydrate. Examples of counter ions of the ferric salt include chloride ions, citrate ions, oxalate ions, paratoluenesulfonate ions, perchlorate ions, hexafluorophosphate ions, tetrafluoroborate ions, etc. When at least one of the perchlorate ions, hexafluorophosphate ions, and tetrafluoroborate ions is used as the counter ion of the ferric salt, a film exhibiting a gloss close to gold can be formed.

[0031] When an oxidizing agent having a counter ion of perchlorate ion, hexafluorophosphate ion, tetrafluoroborate ion, or chloride ion is used, these counter ions remain stably bound to the thiophene polymer, and the metallic luster state can be stably maintained.

[0032] The oxidative polymerization is preferably carried out in a solvent. The solvent is preferably a solvent that dissolves the thiophenes and the oxidizing agent and efficiently polymerizes the thiophenes. The solvent is preferably an organic solvent having high polarity and a certain degree of volatility.

[0033] Examples of the solvent include acetonitrile, nitromethane, γ-butyrolactone, propylene carbonate, N-methylpyrrolidone, dimethylformamide, dimethylsulfoxide, nitromethane, 1-methyl-2-pyrrolidinone, 2-butanone, tetrahydrofuran, acetone, methanol, anisole, chloroform, ethyl acetate, hexane, trichloroethylene, cyclohexanone, dichloromethane, chloroform, ethanol, butanol, pyridine, dioxane, and mixtures thereof.

[0034] As the solvent, from the viewpoint of ensuring that the film containing the thiophene polymer exhibits metallic luster, an aprotic polar solvent is preferable, and at least one selected from the group consisting of acetonitrile, nitromethane, γ-butyrolactone, propylene carbonate, N-methylpyrrolidone, dimethylformamide, and dimethylsulfoxide is more preferable.

[0035] The mass ratio of the solvent to the thiophenes is preferably from 1:0.00007 to 1:7, and more preferably from 1:0.0007 to 1:0.7. For example, when the oxidizing agent is iron(III) perchlorate n-hydrate (2D), the mass ratio of the solvent to the oxidizing agent is preferably solvent:iron(III) perchlorate n-hydrate (2D)=1:0.0006 to 1:6, and more preferably 1:0.006 to 1:0.6. The mass ratio of thiophenes to the oxidizing agent, thiophenes:oxidizing agent, is preferably from 1:0.1 to 1:1000, and more preferably from 1:1 to 1:100.

[0036] The technique of the oxidative polymerization is not particularly limited. The oxidative polymerization may be carried out by adding and dissolving the thiophene and the oxidizing agent in a solvent at once, or by separately preparing a solution in which the thiophene is dissolved in a solvent and a solution in which the oxidizing agent is dissolved in a solvent, and mixing the two solutions to carry out the oxidative polymerization.

[0037] By changing the concentration of thiophenes, the reaction temperature and the reaction time in the oxidative polymerization, the molecular weight of the thiophene polymer can be adjusted.

[0038] The thiophene polymer synthesized by the oxidative polymerization method may be used as it is in the form of a solution, or may be used as a powdered thiophene polymer after removing the solvent.

[0039] The powdered thiophene polymer may contain impurities derived from the oxidizing agent used in the oxidative polymerization. In order to remove the impurities, at least one of the following treatments (a), (b) and (c) may be carried out. (a) The thiophene polymer is washed using a poor solvent. (b) A solution in which a thiophene polymer is dissolved in a good solvent is dropped into a poor solvent to precipitate the thiophene polymer. (c) A poor solvent is added dropwise to a solution in which a thiophene polymer is dissolved in a good solvent, thereby precipitating the thiophene polymer. As the poor solvent, alcohols such as methanol, ethanol, and isopropanol are preferable, and as the good solvent, dimethylformamide, dimethylsulfoxide, and tetrahydrofuran are preferable.

[0040] The thiophene polymer can be synthesized by electrolytic polymerization. The thiophene polymer obtained by electrolytic polymerization can be dissolved in a solvent and used in the embodiments of the present disclosure. The electrolytic polymerization method is a method in which a film made of an insoluble polymer is formed on a conductor by electrooxidizing a monomer in an electrolytic solution prepared by dissolving the monomer in a solvent containing a supporting electrolyte.

[0041] Examples of the solvent in the electrolytic polymerization include water, alcohol, and a mixture thereof. In addition, the solvents described in "Electrochemical Measurement Methods, Vol. 1," pp. 107-114 (Akira Fujishima, Masuo Aizawa, Toru Inoue, Gihodo Publishing, 1984) may be used.

[0042] The supporting electrolyte is preferably an electrolyte that is sufficiently soluble in the solvent and is not easily electrolyzed. In terms of the cation, the supporting electrolyte is preferably a lithium salt, a sodium salt, a potassium salt, a calcium salt, or a tetraalkylammonium salt, and in terms of the anion, the supporting electrolyte is preferably a halide, a sulfate, a nitrate, a phosphate, a perchlorate, a boron trifluoride, or a hexafluorophosphate.

[0043] The concentration of the thiophenes in the electrolytic solution is preferably 0.1 mmol / L or more and the solubility limit or less, and more preferably 1 mmol / L or more and 1 mol / L or less. The concentration of the supporting electrolyte in the electrolytic solution is preferably 0.001 mol / L or more and the solubility or less, and more preferably 0.01 mol / L or more and 1 mol / L or less.

[0044] The electrolytic polymerization method is preferably a three-electrode method using a conductor functioning as a working electrode, a counter electrode, and a reference electrode serving as a potential standard, or a two-electrode method using a conductor functioning as a working electrode and a counter electrode. The three-electrode method is preferred from the viewpoint of polymerizing a desired thiophene polymer with good reproducibility.

[0045] The material of the conductor functioning as the working electrode is preferably a substance stable against electrode oxidation in both the three-electrode and two-electrode systems. For example, an electrode coated with a conductive film such as indium tin oxide or tin oxide (transparent glass electrode, metal electrode, glassy carbon electrode, etc.) is preferable. As the counter electrode, the above-mentioned electrodes, stainless steel, copper plate, or other metal electrodes are preferable. As the reference electrode, an Ag / AgCl electrode or a saturated calomel electrode is preferable.

[0046] When anodizing is performed in the electrolytic polymerization method, it is preferable to use a potential sweep method, which is a process in which a potential is applied while being changed at a constant rate.

[0047] The potential sweep method is preferably performed by sweeping between a negative potential and a positive potential. In this case, the negative potential is preferably in the range of -1.5V to -0.01V, more preferably in the range of -1.0V to -0.1V, and even more preferably in the range of -0.7V to -0.2V. The positive potential is preferably in the range of +1.0V to +3.0V, more preferably in the range of +1.0V to +2.0V, and even more preferably in the range of +1.0V to +1.5V. The sweep rate in the potential sweep method is preferably in the range of 0.1 mV / sec to 10 V / sec, more preferably in the range of 1 mV / sec to 1 V / sec, and further preferably in the range of 2 mV / sec to 300 mV / sec.

[0048] The time for electrolytic polymerization is preferably in the range of 1 second to 5 hours, more preferably in the range of 10 seconds to 1 hour. The temperature of electrolysis during electrolytic polymerization is preferably in the range of -20°C or higher and 60°C or lower.

[0049] Electrolysis during electropolymerization is a reaction that involves little atmospheric components and is carried out at a relatively low potential, so it can be carried out in the air. It is preferable to carry out the electrolysis in a nitrogen gas or argon gas atmosphere in order to avoid the possibility of contaminating the formed film, such as by oxidizing impurities in the electrolyte, but there is little risk of contamination. Nevertheless, since the presence of a large amount of oxygen in the electrolyte may affect the electrode reaction, it is also useful to carry out bubbling with an inert gas (nitrogen gas or argon gas).

[0050] [Polymerization components] The polymerization component is a chemical substance having a polymerizable group, and is at least one of a monomer and an oligomer. The monomer and oligomer may be monofunctional or polyfunctional. The monomer and oligomer may be used alone or in combination of two or more kinds.

[0051] Examples of the monofunctional monomer include monofunctional (meth)acrylates. Examples of the monofunctional (meth)acrylates include caprolactone (meth)acrylate, isodecyl (meth)acrylate, isooctyl (meth)acrylate, isomyristyl (meth)acrylate, isostearyl (meth)acrylate, 2-ethylhexyl-diglycol di(meth)acrylate, 2-hydroxybutyl (meth)acrylate, 2-(meth)acryloyloxyethylhexahydrophthalic acid, neopentyl glycol (meth)acrylic acid benzoate, isoamyl (meth)acrylate, lauryl (meth)acrylate, stearyl (meth)acrylate, butoxyethyl (meth)acrylate, ethoxy-diethylene glycol (meth)acrylate, methoxy-triethylene glycol (meth)acrylate, meth ... Examples of the acrylates include methoxy-polyethylene glycol (meth)acrylate, methoxydipropylene glycol (meth)acrylate, phenoxyethyl (meth)acrylate, phenoxy-polyethylene glycol (meth)acrylate, nonylphenol ethylene oxide adduct (meth)acrylate, tetrahydrofurfuryl (meth)acrylate, isobornyl (meth)acrylate, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, 2-hydroxy-3-phenoxypropyl (meth)acrylate, 2-(meth)acryloyloxyethyl-succinic acid, 2-(meth)acryloyloxyethyl-phthalic acid, 2-(meth)acryloyloxyethyl-2-hydroxyethyl-phthalic acid, and the like. These may be used alone or in combination of two or more. In the present disclosure, "(meth)acrylic" means that it may be either "acrylic" or "methacrylic".

[0052] The bifunctional monomer may be a bifunctional (meth)acrylate. Examples of the bifunctional (meth)acrylate include hydroxypivalic acid neopentyl glycol di(meth)acrylate, alkoxylated hexanediol di(meth)acrylate, polytetramethylene glycol di(meth)acrylate, trimethylolpropane (meth)acrylic acid benzoate, diethylene glycol di(meth)acrylate, triethylene glycol di(meth)acrylate, tetraethylene glycol di(meth)acrylate, polyethylene glycol (200) di(meth)acrylate, polyethylene glycol ( Examples of the di(meth)acrylate include polyethylene glycol (600) di(meth)acrylate, neopentyl glycol di(meth)acrylate, 1,3-butylene glycol di(meth)acrylate, 1,4-butanediol di(meth)acrylate, 1,6-hexanediol di(meth)acrylate, 1,9-nonanediol di(meth)acrylate, dimethylol-tricyclodecane di(meth)acrylate, bisphenol A di(meth)acrylate, and ethoxylated bisphenol A di(meth)acrylate. These may be used alone or in combination of two or more.

[0053] Examples of oligomers having a polymerizable group include urethane (meth)acrylate, polyester (meth)acrylate, epoxy (meth)acrylate, silicon (meth)acrylate, polybutadiene (meth)acrylate, etc. These may be used alone or in combination of two or more.

[0054] The polymerization component is preferably a polyfunctional one from the viewpoint of promoting the polymerization reaction when forming a cured film. The polymerization component is preferably a chain-polymerizable polymerization component from the viewpoint of promoting the polymerization reaction when forming a cured film.

[0055] When the liquid composition according to the present embodiment contains a monomer as a polymerization component but does not contain an oligomer, the content of the monomer is preferably 30% by mass or more, more preferably 35% by mass or more, and even more preferably 40% by mass or more, based on the total solid content of the liquid composition, from the viewpoint of excellent scratch resistance of the cured film. When the liquid composition according to the present embodiment contains a monomer as a polymerization component but does not contain an oligomer, the content of the monomer is preferably 70% by mass or less, more preferably 65% ​​by mass or less, and even more preferably 60% by mass or less, based on the total solid content of the liquid composition, from the viewpoint of inkjet dischargeability of the liquid composition.

[0056] When the liquid composition according to the present embodiment contains an oligomer as a polymerization component but does not contain a monomer, the content of the oligomer is preferably 20% by mass or more, more preferably 25% by mass or more, and even more preferably 30% by mass or more, based on the total solid content of the liquid composition, from the viewpoint of excellent scratch resistance of the cured film. When the liquid composition according to the present embodiment contains an oligomer as a polymerization component but does not contain a monomer, the content of the oligomer is preferably 60% by mass or less, more preferably 55% by mass or less, and even more preferably 50% by mass or less, based on the total solid content of the liquid composition, from the viewpoint of inkjet dischargeability of the liquid composition.

[0057] The content of the polymerizable components in the liquid composition according to this embodiment is preferably from 20% by mass to 70% by mass, more preferably from 25% by mass to 65% by mass, and even more preferably from 30% by mass to 60% by mass, based on the total solid content of the liquid composition.

[0058] The mass ratio of the thiophene polymer to the polymerization component in the liquid composition according to this embodiment is preferably thiophene polymer:polymerization component=1:0.01 to 1:100, more preferably 1:0.05 to 1:50, and even more preferably 1:0.1 to 1:5.

[0059] [Polymerization initiator] The liquid composition according to the present embodiment preferably contains a polymerization initiator from the viewpoint of promoting the polymerization reaction when forming a cured film.

[0060] As the polymerization initiator, from the viewpoint of promoting the polymerization reaction when forming a cured film, at least one of a thermal radical generator and a photoradical generator is preferable. The polymerization initiator may be used alone or in combination of two or more kinds. Examples of the thermal radical generator include azo compounds and organic peroxides. Examples of photoradical generators include hydroxyketones, acylphosphine oxides, benzoins, benzil ketals, aminoketones, titanocenes, bisimidazoles, aromatic ketones, aromatic onium salts, organic peroxides, thio compounds (thioxanthone compounds, thiophenyl group-containing compounds, etc.), hexaarylbiimidazole compounds, ketoxime ester compounds, borate compounds, azinium compounds, metallocene compounds, active ester compounds, compounds having a carbon-halogen bond, and alkylamine compounds.

[0061] The amount of the polymerization initiator contained in the liquid composition according to the present embodiment may be set according to the amount of the polymerization component. The amount of the polymerization initiator is preferably 1% by mass or more and 10% by mass or less, more preferably 2% by mass or more and 8% by mass or less, and even more preferably 3% by mass or more and 6% by mass or less, based on the total solid content of the liquid composition.

[0062] [solvent] The liquid composition according to the present embodiment preferably contains a solvent from the viewpoint of adjusting the substance concentration and viscosity. In the present embodiment, the "solvent" of the liquid composition refers to a component that volatilizes during the formation of the metallic luster film and does not substantially remain in the metallic luster film.

[0063] The solvent is preferably a solvent that dissolves at least the thiophene polymer, and examples thereof include acetonitrile, nitromethane, γ-butyrolactone, propylene carbonate, N-methylpyrrolidone, dimethylformamide, dimethylsulfoxide, nitromethane, 1-methyl-2-pyrrolidinone, 2-butanone, tetrahydrofuran, acetone, methanol, anisole, chloroform, ethyl acetate, hexane, trichloroethylene, cyclohexanone, dichloromethane, chloroform, ethanol, butanol, pyridine, dioxane, and mixtures thereof.

[0064] As the solvent, from the viewpoint of ensuring that the film containing the thiophene polymer exhibits metallic luster, an aprotic polar solvent is preferable, and at least one selected from the group consisting of acetonitrile, nitromethane, γ-butyrolactone, propylene carbonate, N-methylpyrrolidone, dimethylformamide, and dimethylsulfoxide is more preferable.

[0065] The amount of the solvent contained in the liquid composition according to this embodiment is preferably from 0% by mass to 99.9% by mass, more preferably from 1% by mass to 99% by mass, and even more preferably from 5% by mass to 95% by mass, based on the entire liquid composition.

[0066] The viscosity of the liquid composition according to this embodiment is preferably from 1 mPa·s to 30 mPa·s, and more preferably from 2 mPa·s to 20 mPa·s. In this embodiment, the viscosity of the liquid composition is measured using a TV-20 viscometer (Toki Sangyo Co., Ltd.) at a temperature of 23±0.5° C. and a shear rate of 1400 s -1 Measure under the following conditions.

[0067] [Other ingredients] The liquid composition according to the present embodiment may contain various additives, such as a sensitizer, a heat stabilizer, an antioxidant, an anti-reducing agent, an antifoaming agent, a penetrating agent, a leveling agent, a surfactant, a dispersion stabilizer, a viscosity adjuster, a pH adjuster, an ultraviolet absorber, a preservative, and an anti-mold agent.

[0068] <Metallic gloss film> The metallic luster film according to this embodiment is a film formed by curing the liquid composition according to this embodiment. The metallic luster film according to this embodiment has excellent scratch resistance.

[0069] The metallic luster film according to this embodiment can be formed, for example, by applying the liquid composition according to this embodiment onto an article to form a coating film, and then applying at least one of heat and light to the coating film.

[0070] The coating film is preferably formed by an inkjet method. The coating film may also be formed by a screen printing method, an offset printing method, a spin coating method, a bar coating method, a dip coating method, a drop casting method, or the like.

[0071] The temperature of heat or the frequency and intensity of light applied to the coating film is preferably selected according to the type and amount of the polymerization component contained in the liquid composition according to this embodiment, and the type and amount of the polymerization initiator.

[0072] After the metallic luster film is formed, it is preferable to apply pressure to the metallic luster film in order to fix the metallic luster film onto the article. Pressurization includes rubbing.

[0073] The thickness of the metallic luster film is preferably a thickness that exhibits metallic luster, and specifically, is preferably 0.01 μm or more and 200 μm or less.

[0074] The thiophene polymer contained in the metallic luster film preferably has a weight average molecular weight of 200 or more and 30,000 or less, more preferably 500 or more and 20,000 or less, and even more preferably 1,000 or more and 10,000 or less. The molecular weight of the thiophene polymer contained in the metallic luster film is measured, for example, by dissolving the metallic luster film in a solvent and extracting the thiophene polymer.

[0075] <Goods> The article according to this embodiment has the metallic luster film according to this embodiment.

[0076] The article according to the present embodiment is manufactured by forming the metallic gloss film according to the present embodiment on the article. Examples of the article on which the metallic gloss film is formed include furniture, building materials, toys, miscellaneous goods, clothing, paper products, packaging, etc. However, these are merely examples, and there is no particular limitation as long as the article can be formed with the metallic gloss film. The material of the article is preferably resin, glass, paper, etc., from the viewpoint of ease of forming the metallic gloss film. EXAMPLES

[0077] The present embodiment will be described in more detail below by way of examples, but the present embodiment is not limited to the following examples. Unless otherwise specified, "parts" and "%" are by weight. Synthesis, processing, production, etc. were performed at room temperature (25°C ± 3°C) unless otherwise specified.

[0078] <Example 1> [Synthesis of thiophene polymers] 11.4g of 3-methoxythiophene was placed in a three-necked flask, 0.5L of acetonitrile was added, and 3-methoxythiophene was dissolved in acetonitrile. The atmosphere in the three-necked flask was then replaced with nitrogen and cooled to 0°C. A solution in which 101g of iron(III) perchlorate n-hydrate [II] was dissolved in 0.5L of acetonitrile was then added dropwise while maintaining the solution and the reaction system at 5°C or less. The temperature was then raised to room temperature and the mixture was stirred at room temperature for 15 hours. 1L of methanol was then added and the mixture was stirred for 1 hour. The mixture was then subjected to solid-liquid separation using a centrifuge, the solid matter was collected, and dried under reduced pressure at 60°C for 16 hours to obtain 10.5g of a thiophene polymer.

[0079] [Methanol washing] 2.0 g of the synthesized thiophene polymer was placed in a beaker, 50 mL of methanol was added, the liquid temperature was adjusted to 45° C., and the mixture was stirred for 1 hour. Then, solid-liquid separation was performed using a centrifuge, the solid content was placed in a beaker, 50 mL of methanol was added, the liquid temperature was adjusted to 45° C., and the mixture was stirred for 1 hour. Then, solid-liquid separation was performed using a centrifuge, and the solid content was collected and dried under reduced pressure at 60° C. for 16 hours to obtain 1.8 g of a thiophene polymer. The weight average molecular weight of the thiophene polymer after washing with methanol was 3000.

[0080] [Preparation of liquid composition] 100 mg of the thiophene polymer after methanol washing and 100 mg of ethoxylated bisphenol A diacrylate (trade name ABE-300, manufactured by Shin-Nakamura Chemical Co., Ltd.) were dissolved in 10 mL of γ-butyrolactone. 20 mg of a thermal radical generator (trade name AIBN, manufactured by Otsuka Chemical Co., Ltd., 10-hour half-life temperature 65°C) was dissolved therein, and the solution was filtered using a 0.45 μm membrane filter. Ar bubbles were bubbled into the filtrate for 30 minutes to remove oxygen, and a liquid composition was obtained.

[0081] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then placed in a glass sealed container. The air in the sealed container was replaced with dry Ar until the oxygen concentration in the sealed container reached 100 ppm (ppm stands for parts per million, and the oxygen concentration is based on volume). The container was then placed at a temperature of 45°C for 20 minutes and at a temperature of 100°C for 20 minutes. The coating film was thus cured to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0082] [Formation of metallic gloss reference film] 100 mg of the thiophene polymer after washing with methanol was dissolved in 10 mL of γ-butyrolactone and filtered using a 0.45 μm membrane filter to obtain a thiophene polymer solution. The thiophene polymer solution was drop-cast onto a washed glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, then at a temperature of 45° C. for 20 minutes and at a temperature of 100° C. for 20 minutes. In this way, a metallic gloss reference film was formed. The thickness of the metallic gloss reference film was about 1.0 μm.

[0083] <Examples 2 to 7> In the same manner as in Example 1, thiophene polymers with different weight-average molecular weights were synthesized by changing the concentration of 3-methoxythiophene, the reaction temperature, and the reaction time in the synthesis of the thiophene polymer, and the same methanol washing as in Example 1 was performed. Thus, thiophene polymers having the weight-average molecular weights shown in Table 1 were obtained. Then, in the same manner as in Example 1, a liquid composition was prepared and a metallic gloss film was formed. Also, in the same manner as in Example 1, a thiophene polymer solution was prepared and a metallic gloss reference film was formed. The thickness of the metallic gloss film and the metallic gloss reference film was about 1.0 μm.

[0084] <Comparative Example 1> Using the thiophene polymer synthesized and washed with methanol in Example 1, a metallic luster film was formed in the same manner as in [Formation of metallic luster reference film] in Example 1. The thickness of the metallic luster film was about 1.0 μm.

[0085] <Comparative Example 2> [Preparation of liquid composition] 100 mg of the thiophene polymer synthesized and washed with methanol in Example 1 and 100 mg of the polyester resin were dissolved in 10 mL of γ-butyrolactone and filtered using a 0.45 μm membrane filter to obtain a liquid composition.

[0086] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then left at a temperature of 45°C for 20 minutes. The coating film was dried to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0087] [Formation of metallic gloss reference film] A metallic luster reference film was formed in the same manner as in [Formation of metallic luster reference film] of Example 1. The thickness of the metallic luster reference film was about 1.0 μm.

[0088] <Example 8> [Preparation of liquid composition] 100 mg of the thiophene polymer synthesized and washed with methanol in Example 1, 50 mg of polyethylene glycol diacrylate (product name SR344, manufactured by Sartomer Japan), and 50 mg of trifunctional urethane acrylate oligomer (product name CN929: manufactured by Sartomer Japan) were dissolved in 10 mL of γ-butyrolactone. 20 mg of a photoradical generator (product name Darocur 1173) was dissolved therein, and the solution was filtered using a 0.45 μm membrane filter. Ar bubbles were bubbled into the filtrate for 30 minutes to remove oxygen, and a liquid composition was obtained.

[0089] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then irradiated with ultraviolet light under the following conditions. The coating film was thus cured to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0090] -Ultraviolet irradiation conditions- Lamp type: Metal halide lamp ·Illuminance: 200mW / cm 2 Number of exposures: 30 Irradiation height: 5mm

[0091] [Formation of metallic gloss reference film] A metallic luster reference film was formed in the same manner as in [Formation of metallic luster reference film] of Example 1. The thickness of the metallic luster reference film was about 1.0 μm.

[0092] <Example 9> [Preparation of liquid composition] 100 mg of the thiophene polymer synthesized and washed with methanol in Example 1, 5 mg of polyethylene glycol diacrylate (manufactured by Sartomer Japan Co., Ltd.), and 95 mg of ethoxylated bisphenol A diacrylate were dissolved in 10 mL of γ-butyrolactone. 20 mg of a thermal radical generator (trade name AIBN, manufactured by Otsuka Chemical Co., Ltd.; 10-hour half-life temperature 65° C.) was dissolved therein, and the solution was filtered using a 0.45 μm membrane filter. Ar bubbles were bubbled into the filtrate for 30 minutes to remove oxygen, and a liquid composition was obtained.

[0093] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then placed in a glass sealed container. The air in the sealed container was replaced with dry Ar until the oxygen concentration in the sealed container reached 100 ppm. The container was then placed at a temperature of 45°C for 20 minutes and at a temperature of 100°C for 20 minutes. The coating film was thus cured to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0094] [Formation of metallic gloss reference film] A metallic luster reference film was formed in the same manner as in [Formation of metallic luster reference film] of Example 1. The thickness of the metallic luster reference film was about 1.0 μm.

[0095] <Example 10> [Preparation of liquid composition] A liquid composition was obtained in the same manner as in [Preparation of liquid composition] of Example 1, except that propylene carbonate was used instead of γ-butyrolactone.

[0096] [Formation of metallic gloss film] Using the above composition, a metallic gloss film was formed in the same manner as in [Formation of metallic gloss film] of Example 1. The metallic gloss film had a thickness of about 1.0 μm.

[0097] [Formation of metallic gloss reference film] Except for using propylene carbonate instead of γ-butyrolactone, a metallic luster reference film was formed in the same manner as in [Formation of metallic luster reference film] of Example 1. The thickness of the metallic luster reference film was about 1.0 μm.

[0098] <Example 11> [Preparation of liquid composition] A liquid composition was obtained in the same manner as in [Preparation of liquid composition] of Example 1, except that a mixed solvent of γ-butyrolactone / acetonitrile=1 / 1 was used instead of γ-butyrolactone.

[0099] [Formation of metallic gloss film] Using the above composition, a metallic gloss film was formed in the same manner as in [Formation of metallic gloss film] of Example 1. The metallic gloss film had a thickness of about 1.0 μm.

[0100] [Formation of metallic gloss reference film] A metallic luster reference film was formed in the same manner as in [Formation of metallic luster reference film] of Example 1, except that a mixed solvent of γ-butyrolactone / acetonitrile = 1 / 1 was used instead of γ-butyrolactone. The thickness of the metallic luster reference film was about 1.0 μm.

[0101] <Example 12> [Synthesis of thiophene polymers] 3.1 g of 3-butoxythiophene was placed in a three-necked flask, 0.1 L of acetonitrile was added, and 3-butoxythiophene was dissolved in acetonitrile. The atmosphere in the three-necked flask was then replaced with nitrogen and cooled to 0°C. A solution in which 20 g of iron (III) perchlorate n-hydrate [II] was dissolved in 0.1 L of acetonitrile was then added dropwise while maintaining the solution and the reaction system at 5°C or less. The temperature was then raised to room temperature and the mixture was stirred at room temperature for 15 hours. 0.2 L of methanol was then added and the mixture was stirred for 1 hour. The mixture was then subjected to solid-liquid separation using a centrifuge, and the solid content was collected.

[0102] [Precipitation and methanol washing] The collected solid was dissolved in 100 mL of dimethylformamide. While stirring this solution, 1 L of isopropyl alcohol was dropped over 30 minutes to gradually precipitate the solid. Then, solid-liquid separation was performed using a centrifuge, the solid was taken in a beaker, 50 mL of methanol was added, the liquid temperature was adjusted to 45°C, and the mixture was stirred for 1 hour. Then, solid-liquid separation was performed using a centrifuge, the solid was collected, and dried at 60°C under reduced pressure for 16 hours to obtain 1.9 g of a thiophene polymer. The weight average molecular weight of the thiophene polymer after washing with methanol was 3200.

[0103] [Preparation of liquid composition] 100 mg of the thiophene polymer after methanol washing and 100 mg of ethoxylated bisphenol A diacrylate (trade name ABE-300, manufactured by Shin-Nakamura Chemical Co., Ltd.) were dissolved in 10 mL of γ-butyrolactone. 20 mg of a thermal radical generator (trade name AIBN, manufactured by Otsuka Chemical Co., Ltd., 10-hour half-life temperature 65°C) was dissolved therein, and the solution was filtered using a 0.45 μm membrane filter. Ar bubbles were bubbled into the filtrate for 30 minutes to remove oxygen, and a liquid composition was obtained.

[0104] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then placed in a glass sealed container. The air in the sealed container was replaced with dry Ar until the oxygen concentration in the sealed container reached 100 ppm. The container was then placed at a temperature of 45°C for 20 minutes and at a temperature of 100°C for 20 minutes. The coating film was thus cured to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0105] [Formation of metallic gloss reference film] 100 mg of the thiophene polymer after washing with methanol was dissolved in 10 mL of γ-butyrolactone and filtered using a 0.45 μm membrane filter to obtain a thiophene polymer solution. The thiophene polymer solution was drop-cast onto a washed glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, then at a temperature of 45° C. for 20 minutes and at a temperature of 100° C. for 20 minutes. In this way, a metallic gloss reference film was formed. The thickness of the metallic gloss reference film was about 1.0 μm.

[0106] <Example 13> [Synthesis of thiophene polymers] 0.02g of 3-methylthiophene and 2.05g of 3-methoxythiophene were placed in a three-necked flask, and 0.1L of acetonitrile was added to dissolve the thiophenes in the acetonitrile. The atmosphere in the three-necked flask was then replaced with nitrogen and cooled to 0°C. A solution in which 20g of iron(III) perchlorate n-hydrate [II] was dissolved in 0.1L of acetonitrile was then added dropwise while maintaining the solution and the reaction system at 5°C or less. The temperature was then raised to room temperature and the mixture was stirred at room temperature for 15 hours. 0.2L of methanol was then added and the mixture was stirred for 1 hour. The mixture was then subjected to solid-liquid separation using a centrifuge, and the solids were collected.

[0107] [Precipitation and methanol washing] The collected solid was dissolved in 100 mL of dimethylformamide. While stirring this solution, 1 L of isopropyl alcohol was dropped over 30 minutes to gradually precipitate the solid. Then, solid-liquid separation was performed using a centrifuge, the solid was taken in a beaker, 50 mL of methanol was added, the liquid temperature was adjusted to 45°C, and the mixture was stirred for 1 hour. Then, solid-liquid separation was performed using a centrifuge, the solid was collected, and dried at 60°C under reduced pressure for 16 hours to obtain 1.9 g of a thiophene polymer. The weight average molecular weight of the thiophene polymer after washing with methanol was 3300.

[0108] [Preparation of liquid composition] 100 mg of the thiophene polymer after methanol washing and 100 mg of ethoxylated bisphenol A diacrylate (trade name ABE-300, manufactured by Shin-Nakamura Chemical Co., Ltd.) were dissolved in 10 mL of γ-butyrolactone. 20 mg of a thermal radical generator (trade name AIBN, manufactured by Otsuka Chemical Co., Ltd., 10-hour half-life temperature 65°C) was dissolved therein, and the solution was filtered using a 0.45 μm membrane filter. Ar bubbles were bubbled into the filtrate for 30 minutes to remove oxygen, and a liquid composition was obtained.

[0109] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then placed in a glass sealed container. The air in the sealed container was replaced with dry Ar until the oxygen concentration in the sealed container reached 100 ppm. The container was then placed at a temperature of 45°C for 20 minutes and at a temperature of 100°C for 20 minutes. The coating film was thus cured to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0110] [Formation of metallic gloss reference film] 100 mg of the thiophene polymer after washing with methanol was dissolved in 10 mL of γ-butyrolactone and filtered using a 0.45 μm membrane filter to obtain a thiophene polymer solution. The thiophene polymer solution was drop-cast onto a washed glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, then at a temperature of 45° C. for 20 minutes and at a temperature of 100° C. for 20 minutes. In this way, a metallic gloss reference film was formed. The thickness of the metallic gloss reference film was about 1.0 μm.

[0111] <Example 14> [Synthesis of thiophene polymers] 0.03g of 3,4-ethylenedioxythiophene and 2.05g of 3-methoxythiophene were placed in a three-necked flask, and 0.1L of acetonitrile was added to dissolve the thiophenes in the acetonitrile. The atmosphere in the three-necked flask was then replaced with nitrogen and cooled to 0°C. A solution in which 20g of iron(III) perchlorate n-hydrate [II] was dissolved in 0.1L of acetonitrile was then added dropwise while maintaining the solution and the reaction system at 5°C or less. The temperature was then raised to room temperature and the mixture was stirred at room temperature for 15 hours. 0.2L of methanol was then added and the mixture was stirred for 1 hour. The mixture was then subjected to solid-liquid separation using a centrifuge, and the solid content was collected.

[0112] [Precipitation and methanol washing] The collected solid was dissolved in 100 mL of dimethylformamide. While stirring this solution, 1 L of isopropyl alcohol was dropped over 30 minutes to gradually precipitate the solid. Then, solid-liquid separation was performed using a centrifuge, the solid was taken in a beaker, 50 mL of methanol was added, the liquid temperature was adjusted to 45°C, and the mixture was stirred for 1 hour. Then, solid-liquid separation was performed using a centrifuge, the solid was collected, and dried at 60°C under reduced pressure for 16 hours to obtain 1.9 g of a thiophene polymer. The weight average molecular weight of the thiophene polymer after washing with methanol was 3100.

[0113] [Preparation of liquid composition] 100 mg of the thiophene polymer after methanol washing and 100 mg of ethoxylated bisphenol A diacrylate (trade name ABE-300, manufactured by Shin-Nakamura Chemical Co., Ltd.) were dissolved in 10 mL of γ-butyrolactone. 20 mg of a thermal radical generator (trade name AIBN, manufactured by Otsuka Chemical Co., Ltd., 10-hour half-life temperature 65°C) was dissolved therein, and the solution was filtered using a 0.45 μm membrane filter. Ar bubbles were bubbled into the filtrate for 30 minutes to remove oxygen, and a liquid composition was obtained.

[0114] [Formation of metallic gloss film] The liquid composition was drop cast onto a cleaned glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, and then placed in a glass sealed container. The air in the sealed container was replaced with dry Ar until the oxygen concentration in the sealed container reached 100 ppm. The container was then placed at a temperature of 45°C for 20 minutes and at a temperature of 100°C for 20 minutes. The coating film was thus cured to form a metallic gloss film. The metallic gloss film had a thickness of about 1.0 μm.

[0115] [Formation of metallic gloss reference film] 100 mg of the thiophene polymer after washing with methanol was dissolved in 10 mL of γ-butyrolactone and filtered using a 0.45 μm membrane filter to obtain a thiophene polymer solution. The thiophene polymer solution was drop-cast onto a washed glass substrate to form a coating film. The glass substrate with the coating film was left at room temperature for 10 minutes, then at a temperature of 45° C. for 20 minutes and at a temperature of 100° C. for 20 minutes. In this way, a metallic gloss reference film was formed. The thickness of the metallic gloss reference film was about 1.0 μm.

[0116] <Performance evaluation> [Gloss of metallic gloss film] Using a UV-2600 UV-Visible Spectrophotometer (Shimadzu Corporation), light with a wavelength of 600 nm was irradiated to measure the regular reflectance (%) of the metallic gloss film and metallic gloss reference film. In addition, the color of the metallic gloss film and metallic gloss reference film was observed with the naked eye under a fluorescent lamp of about 500 lux. Based on the regular reflectance and color, the gloss was classified as follows. The results are shown in Table 1.

[0117] A: The difference in regular reflectance between the metallic luster film and the metallic luster reference film is 5% or less, and the metallic luster film and the metallic luster reference film have the same color tone. B: The difference in regular reflectance between the metallic luster film and the metallic luster reference film is more than 5% and not more than 10%, and the metallic luster film and the metallic luster reference film have the same color tone. C: The difference in regular reflectance between the metallic gloss film and the metallic gloss reference film is more than 5% and not more than 10%, and the metallic gloss film has a slightly blackish color (sufficient for practical use). D: The difference in regular reflectance between the metallic luster film and the metallic luster reference film exceeds 10%, and the metallic luster film and the metallic luster reference film cannot be said to have the same color tone (not suitable for practical use).

[0118] [Scratch resistance of metallic gloss film] The film strength of the metallic gloss film was evaluated according to JIS K5600-5-4:1999 "Scratch hardness (pencil method)". The pencils used were Mitsubishi Pencil Hi-Uni (hardness: 10H, 9H, 8H, 7H, 6H, 5H, 4H, 3H, 2H, H, F, HB, B, 2B, 3B, 4B, 5B, 6B, 7B, 8B, 9B, 10B). The hardest hardness that did not leave scratches on the metallic gloss film is shown in Table 1.

[0119] [Inkjet ejection properties of liquid composition] An inkjet printer "EPSON PX-1004" was prepared, and after the ejection head was washed with the solvent used in each Example or Comparative Example, the liquid composition of each Example or Comparative Example was injected into the ink cartridge. A straight line of 600 dpi was printed on plain paper using the inkjet printer, and the edge of the straight line was observed and classified as follows. The results are shown in Table 1.

[0120] A: Even when observed at 100x magnification with a magnifying glass, no chips can be seen on the straight edges. B: No chipping is seen on the straight edge when observed with the naked eye, but chipping is seen on the straight edge when observed with a magnifying glass at 100 parts per centimeter. The frequency of chipping seen with a magnifying glass is 1 to 5 places per 1 cm length, which is not a problem in actual use. C: Chips are visible to the naked eye on the straight edge. The frequency of chips visible to the naked eye is 1 to 5 chips per 1 cm length. D: Chips are visible to the naked eye along straight edges. The frequency of chips visible to the naked eye is 6 or more per cm length. F: Unable to discharge.

[0121] [Table 1]

Claims

1. a thiophene polymer; at least one polyfunctional polymerization component selected from the group consisting of monomers and oligomers; A polymerization initiator; an aprotic polar solvent; the thiophene polymer contains at least a polymer in which an alkoxythiophene is polymerized, The weight average molecular weight of the thiophene polymer is 1,000 or more and 10,000 or less. Liquid composition.

2. The liquid composition according to claim 1 , wherein the multifunctional polymerizable component comprises a chain-polymerizable polymerizable component.

3. The liquid composition according to claim 1 or 2, wherein the polymerization initiator comprises at least one selected from the group consisting of a thermal radical generator and a photoradical generator.

4. The aprotic polar solvent comprises at least one selected from the group consisting of acetonitrile, nitromethane, γ-butyrolactone, propylene carbonate, N-methylpyrrolidone, dimethylformamide and dimethylsulfoxide. The liquid composition according to any one of claims 1 to 3.

5. A liquid composition described in any one of claims 1 to 4, wherein the alkoxythiophene includes an alkoxythiophene having an alkoxy group with 1 or more and 8 or less carbon atoms.

6. the thiophene polymer includes a polymer in which at least an alkylthiophene is polymerized, The liquid composition according to any one of claims 1 to 5, wherein the alkylthiophene includes an alkylthiophene having an alkyl group having 1 to 8 carbon atoms.

7. A metallic gloss film obtained by curing the liquid composition according to any one of claims 1 to 6.

8. An article having the metallic luster film according to claim 7.

Citation Information

Patent Citations

  • Voice recognition equipment

    JP1985031197A

  • Method for sensing stereoscopic image of wider view angle than angle of each photograph by two seets of photographs, and stereoscopic photograph used therefor, and stereoscopic camera, and viewer for stereoscopic photograph

    JP1988008624A

  • Resin laminate and process for manufacturing the same

    JP2010030249A

  • Composition for forming conductive film, and laminated body with conductive film

    JP2010103106A

  • Antistatic Anti-glare antireflection coating composition, and antistatic Anti-glare antireflection film, polarizer and display device using the same

    JP2013105178A